Evaluation of Eyelid Lesions at a Tertiary Care Hospital, Jinnah Postgraduate Medical Centre (JPMC), Karachi - Mahmood Saeed, Zia Ghaffar, Fouzia Farhat, Qamar Jamal (Pakistan Journal of Ophthalmology, 2010)
Purpose: To review the pathological lesions of eyelid and to find out their relative frequency. Materials and Methods: The study was conducted during seven years between 1995 to 2001 at Basic Medical Sciences Institute (BMSI), Jinnah Postgraduate Medical Centre (JPMC), Karachi. In this study evaluation of 258 cases of eyelid lesions were received during our study period. By examining 5?m thick slides prepared from paraffin embedded blocks and staining with different stains, histopathological diagnoses confirmed by performing microscopy was under x10, x40, and x100 magnification. Results: A definite histopathological diagnosis was made in 238 cases. Out of which 105 (44.11%) cases were benign, 87 (36.99%) cases malignant, 39 (16.39%) cases non-neoplastic tumour-like lesions, and 7 (2.94%) cases were pre-malignant lesions during our seven years study period. Conclusion: All the clinically confusing and worrisome eyelid lesions should be immediately biopsied to get an exact diagnosis at cellular level. Confirmation of surgical margin for tumour clarity cannot be over-emphasized in oculoplastic reconstructions.